Eucalyptus essential oil exerted a sedative-hypnotic effect by influencing brain neurotransmitters and gut microbes via the gut microbiota-brain axis - Li, Xuejiao; Zhang, Yuanyi; Zhang, Qian; Cao, Aizhi; Feng, Jie (Frontiers in Pharmacology, 2024)
Sleep disorders are becoming more and more common, leading to many health problems.However, most of current available medications to treat sleep disorders are addictive and even impair cognitive abilities. Therefore, it is important to find a natural and safe alternative to treat sleep disorders. In this study, twenty-four 8-week-old male ICR mice (25 ± 2 g) were equally divided into three groups: the control group (gavage of 0.9% saline), the eucalyptus essential oil (EEO) group (10 mg/kg B.W.), and the diazepam group (1 mg/kg B.W.). Firstly, open field test and sleep induction test were used to determine the sedative-hypnotic effect of EEO. Secondly, the effect of EEO on neurotransmitters in the mice brain was determined. Finally, based on the gut microbiota-brain axis (GMBA), the effect of EEO on the intestinal flora of mice was explored. It was found that EEO significantly reduce the activity and prolong the sleep duration of mice, exhibiting a good sedative-hypnotic effect. In the brain, EEO could increase the levels of sleep-promoting neurotransmitters, such as glutamine, Gamma-aminobutyric acid (GABA), glycine, tryptophan, N-acetylserotonin, and 5-hydroxyindoleacetic acid (5-HIAA). In the intestine, EEO was found to increase the diversity of gut microbes, the abundance of short chain fatty acid (SCFA) producing flora, and the abundance of functional flora synthesizing GABA and glycine neurotransmitters. These studies suggested that EEO exerted a sedative-hypnotic effect by acting on gut microbes and neurotransmitters in the brain. EEO has the potential to become a natural and safe alternative to traditional hypnotic sedative drugs.